A vida que pulsa: forma????o e trabalho na enfermagem e o l??cus da autonomia para exercer o cuidar. - Sanino, Giane Elis de Carvalho (2013)
The theme of this research was the relationship between the training of nurses, their work and the society where they develop themselves . The problem that this research was to investigate was the formation of the nurse in the capitalist consumer society. The following hypotheses broke up : 1 ) the training of nurses in the context of current cultural and socio-economic system has taken on a connotation of pseudo-training , fragmented , one-dimensional , that is, more focused on the health-illness binomial, focusing on the technical and scientific aspects , unarticulated from needs of the social reality in which graduates of nursing courses will be inserted . 2 ) the construction of an education for autonomy and emancipation becomes possible , raising a critical stance against the socioeconomic , political and cultural environment in which the nursing professionals performs their activity , promoting the autonomy and self-development , which trespass the purely technical and biological aspects , in order to put the nursing knowledge in the unity of the human being , concerning their fundamental needs, in order to overcome the reductionism of the health -disease binomial . Nursing work, when coated in an economic sense, can be in contradiction with what one wishes for care, based on the epidemiological profile of the health-disease process. 3 ) oral histories of nurses and nursing teachers' lives can contribute to think of an alternative pedagogical project in nursing . The objectives of the study were: a) analyze how nurses are trained, concerning the decisive macrosocial structures to the health-disease process, b) describe how nurses teaching nursing and nurses comprise the construction of the training process and the possibility of developing autonomy in the exercise of care, c ) identify whether there is a possibility to overcome, in the training project , the hegemony of capitalism and its scientific-technical and consumerist universality in healthcare . The subjects were four nurses, two of them also educators, working directly with the training of nurses. The oral history of life was used as empirical research methodology. The theoretical reference used was the Critical Theory of Frankfurt School. From results we can note that life pulsates in nursing, in search of autonomy to exercise the care, despite the complex relationship between the prevailing scientific model, public health policies, management practices, training policies and practices of training. In this scenario, there is a need to rethink the model of training of health professionals from the understanding that health and disease are ways in which life is manifested, they are subjective and unique experiences that go beyond the questions posed by capitalism, whence the tension between the disease's subjectivity and the objectivity of this model of promoting health is presented.